Femicide: A Retrospective Study in Indian Scenario - Mohanty, Sujan Kumar; Maddileti, G Bala; Kumar, Virendra; Mohanty, Sachidananda; Ready, K Bhaskar; Bhuvan , V (Journal of Indian Academy of Forensic Medicine, 2015)
Femicide is considered as killing of women, regardless of motive or perpetrator status. In India,  violence and crimes against women like rape, kidnapping & abduction, murder and dowry death have  increased over the years and evolved as a major social problem. To find out correlation between the  crime and social status of victim, the present study was carried out to analyse different aspects of  femicide from victims‟ profile. This retrospective study analysed 150 cases of femicide, which had been  brought for medico-legal autopsy during a period of five years (November 2006 to October 2011).  Females of 11-40 years of age were the common victims. In most of the killings, the alleged offender was  a male relative of the victim. In majority of the cases, the weapons used were either hard & blunt or sharp  cutting without any defence wounds. Death was commonly due to cranio cerebral injuries. Majority of the  victims were illiterate, married, hailing from rural population & economically backward class and  housewives by occupation. The findings may help the State and law making agencies to improve certain  social issues, which indirectly reduce the crime against women.
Keywords: Autopsy; Familial Disharmony; Femicide; Own House; Relative